Application of Electrical Properties to Differentiate Lard from Tallow and Palm Oil - . Sucipto; T Djatna; . Irzaman; Tun Tedja I; A M Fauzi (Faculty of Animal Science, Bogor Agricultural University, 2013)
This study aimed to differentiate lard from tallow and palm oil based on its electrical properties, namely conductance, impedance and capacitance. These properties were measured at spectra frequencies of 4.20 to 5.00 MHz in room temperature (26-27 oC). Statistic multivariate that consist on principal component analysis (PCA) and cluster analysis (CA) were used to evaluate the data. The results showed that lard and tallow can be differentiated using whole parameters electrical properties of materials. On the other hand, lard and palm oil can only be differentiated using part of the material electrical properties. Good performance of differentiation process was obtained using PCA model at 4.91 to 4.98 MHz. The first two components of PCA, which was derived from conductance, impedance and capacitance, contributed more than 90% of the total variances. CA showed that lard and tallow are different groups based on the Euclidean distance of each electrical properties. This technique can be potentially developed as an electrical sensor for differentiation lard to tallow and palm oil.